Adverse Childhood Experiences and Mindfulness in Chinese College Students During the COVID-19 Pandemic - Chienchung Huang; Meifen Yang; Yun Geng; Yafan Chen; Shannon P. Cheung; Guosheng Deng; Qiang Dong; Hongwei Hu; Kai Hua; Jinyu Liao; Yuanfa Tan; Bin Tu; et al. (Frontiers in Psychiatry, 2021)
Mindfulness has been found to have many positive effects on life outcomes, including mental health and educational achievement. However, less is known about the antecedents of mindfulness, particularly in Chinese college students. This study examines the effect of adverse childhood experiences (ACEs) on mindfulness among Chinese college students in September 2020, during the COVID-19 pandemic. We hypothesized that ACEs negatively affected students' mindfulness. The data were collected from 1,871 college students from 12 colleges across China. The results aligned with our hypothesis that ACEs was negatively associated with mindfulness. In particular, emotional abuse and neglect in childhood appear to have the most negative effects on mindfulness compared to other dimensions of ACEs such as physical abuse and household challenges.